PENGARUH PEMBELAJARAN BERBASIS SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATICS TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 5 PADANG - Waldi, Elda Wati (Departemen Matematika, 2024)
This study aimed to assess the efficacy of STEM-based teaching in promoting learners' math communication skills. It also describes the progress of their math communication skills during the intervention. The research sample was taken from randomly selected VIII grade students of SMP Negeri 5 Padang. The research design chosen was Nonequivalent Posttest Only Control Group Design. The research instruments were quizzes and tests specifically designed to assess mathematical communication skills. The research data were analyzed descriptively and hypothesis testing. Descriptive data analysis showed that this ability had developed in the experimental class. The results of the hypothesis test showed that mathematical communication skills increased with STEM-based learning.Keywords– Mathematical Communication Skills, STEM Based Learning, Direct Learning